Urinary type IV collagen is related to left ventricular diastolic function and brain natriuretic peptide in hypertensive patients with prediabetes - Iida, Masato; Yamamoto, Mitsuru; Ishiguro, Yuko S.; Yamazaki, Masatoshi; Ueda, Norihiro; Honjo, Haruo; Kamiya, Kaichirou (Journal of diabetes and its complications, 2014)
Urinary type IV collagen is an early biomarker of diabetic nephropathy. Concomitant prediabetes (the early stage of diabetes) was associated with left ventricular (LV) diastolic dysfunction and increased brain natriuretic peptide (BNP) in hypertensive patients. We hypothesized that urinary type IV collagen may be related to these cardiac dysfunctions. We studied hypertensive patients with early prediabetes (HbA1c <5.7% and fasting glucose >110, n=18), those with prediabetes (HbA1c 5.7–6.4, n=98), and those with diabetes (HbA1c>6.5 or on diabetes medications, n=92). The participants underwent echocardiography to assess left atrial volume/body surface area (BSA) and the ratio of early mitral flow velocity to mitral annular velocity (E/e’). Left ventricular diastolic dysfunction (LVDD) was defined if patients had E/e’≥15, or E/e’=9–14 accompanied by left atrial volume/BSA≥32ml/mm2. Urinary samples were collected for type IV collagen and albumin, and blood samples were taken for BNP and HbA1c. Urinary type IV collagen and albumin increased in parallel with the deterioration of glycemic status. In hypertensive patients with prediabetes, subjects with LVDD had higher levels of BNP and urinary type IV collagen than those without LVDD. In contrast, in hypertensive patients with diabetes, subjects with LVDD had higher urinary albumin and BNP than those without LVDD. Urinary type IV collagen correlated positively with BNP in hypertensive patients with prediabetes, whereas it correlated with HbA1c in those with diabetes. In hypertensive patients with prediabetes, urinary type IV collagen was associated with LV diastolic dysfunction and BNP.